The Undercurrent Coming to the Surface: Pentecostal Strategies, Entrepreneurship, and the Nation State in the Chinese World. (1st May 2020) - Cao, Nanlai
Abstract : This paper explores the convergence and divergence in the development of Chinese Christianity and the global surge of Pentecostalism by focusing on the evolution and expansion of an indigenous Pentecostal sector in Chinese Christianity. Drawing on extended ethnographic fieldwork among prosperous urban church communities in coastal southeast China and the growing Chinese merchant diaspora in Europe, I show that the Pentecostal undercurrent sustained by mostly charismatic women and their rural networks has come to surface and been increasingly transformed by an entrepreneurial male-dominated prosperity gospel. The surfacing of this Chinese Pentecostal undercurrent under the current context of China's state-led modernization and global business outreach has resulted in a combination of entrepreneurial logic, spiritual renewal, and emotional nationalism in a self-envisioned Chinese-led global mission movement, contributing to the growth of a neo-Pentecostal sector of post-Mao, globalizing Chinese Christianity.